Aesthetic surgery: a new trend in sexology - Błażejewska, Anita; Nowakowski, Artur; Barwijuk, Andrzej; Lew-Starowicz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2010)
The purpose of this article is to review currently available methods of plastic correction of female external sexual organs and to delineate their advantages and limitations.